Targeting cancer cachexia: Molecular mechanisms and clinical study - Yong‐Fei Wang; Zi‐Yi An; Dong‐Hai Lin; Wei‐Lin Jin (MedComm)
Abstract Cancer cachexia is a complex systemic catabolism syndrome characterized by muscle wasting. It affects multiple distant organs and their crosstalk with cancer constitute cancer cachexia environment. During the occurrence and progression of cancer cachexia, interactions of aberrant organs with cancer cells or other organs in a cancer cachexia environment initiate a cascade of stress reactions and destroy multiple organs including the liver, heart, pancreas, intestine, brain, bone, and spleen in metabolism, neural, and immune homeostasis. The role of involved organs turned from inhibiting tumor growth into promoting cancer cachexia in cancer progression. In this review, we depicted the complicated relationship of cancer cachexia with the metabolism, neural, and immune homeostasis imbalance in multiple organs in a cancer cachexia environment and summarized the treatment progress in recent years. And we discussed the molecular mechanism and clinical study of cancer cachexia from the perspective of multiple organs metabolic, neurological, and immunological abnormalities. Updated understanding of cancer cachexia might facilitate the exploration of biomarkers and novel therapeutic targets of cancer cachexia.